Smart Pump Operation Monitoring And Notification (PuMa) Via Telegram Social Messaging Application - Mohamad Hanif Md Saad; Rabiah Adawiyah Shahad; Mohamad Zaki Sarnon; Muhammad Faiz Mohd Shukri; Aini Hussain (Society of Visual Informatics, 2017)
Water supply system contains hydraulic components to supply water. The pumps are an important part in water distribution system and need to be well maintained for most of the time. The failure of pump operating system will result in the water shortage inside water tank. This phenomenon might occur due to the tripped pump and power. This paper proposed a remote monitoring and notification system applied in the pump house with the used of Complex Event Processing tools. Whereas, the notification system that act as an output adapter uses a Telegram Social Messaging application. The study is about how fast the notification system between using SMS and Telegram as an output adapter in the pump operation.